On The Controlled Chaos of S-Iteration According to Lyapunov Exponent and Certain Control Mechanisms in Discrete Dynamical Systems - Sekman, Derya; Karakaya, Vatan (UNIV PUNJAB, DEPT MATHEMATICS, 2023)
In this paper, our aim is to establish the control mechanism of the iteration process defined as S-iteration in the literature. First of all, it is to determine the dynamics of a system with chaotic property under S- iteration. Afterward, we investigate the stability state of the chaotic sys-tem under this iteration with the parameters of the S-iteration. In addition, using the chaotic logistic system, we will illustrate the theoretical results in this example in the MATLAB program. Finally, we will examine the periodic state of the S-iteration and investigate the cases in which the pe-riodic behavior is stable or unstable of the S-iteration with the Lyapunov exponent.
Keywords: Controlling chaos; S-iteration process; Dynamical systems; Lyapunov expo-nent; Fixed point; Stability; FIXED-POINTS; Mathematics